Profitability of Islamic Commercial Banks in Indonesia - Tho'in, Muhammad (MEC-J (Management and Economics Journal), 2019)
This study aims to determine the profitability of Islamic commercial banks in Indonesia reviwed from the effect of NPF ratio and CAR ratio as intervening variable to ROA ratio in 2014-2016. The sampling technique of this research uses purposive sampling with the criteria of Islamic Commercial Banks which are registered in Financial Services Authority during period 2014 until 2016 and Islamic Banks which are consistently publish quarterly report period 2014-2016. The results show that there are 10 BUS with quarterly data amounting to 120. This method of this research uses calculating path analysis method with the help of SPSS 23 program. The test that has been done shows that the NPF ratio has significant effect to ROA ratio which means that the bigger NPF ratio, the bigger cost of eliminating the financing reserve which resulted the income of Islamic commercial bank is decreasing, so it will have an impact to the decrease of ROA ratio.  The NPF ratio significantly influences the CAR ratio, which means that the greater financing risk faced by Islamic commercial banks will increase the formation of allowance for earning assets losses from the equity held, thereby reducing the share of equity which is the component of the capital adequacy. CAR ratios are able to mediate an indirect effects of NPF ratios to ROA ratios.